Tuning diffusion paths in shaped ceria nanocrystals. Issue 27 (17th June 2019) - Esposito, Vincenzo; Kabir, Ahsanul; Rosa, Massimo; Van Nong, Ngo; Rodrigues, Thenner S.; Rodrigues, Lays N.; Machado, Marina F. S.; Moraes, Letícia P. R.; Marani, Debora; Fonseca, Fabio Coral
Abstract : Mass diffusion controls material structuring from the atomic to the macro-scale defining properties and functionalities. Abstract : Mass diffusion controls material structuring from the atomic to the macro-scale defining properties and functionalities. We show here that surface energy in Ce0.9 Gd0.1 O3-d shaped nanocrystals, i.e. nanocubes, nanorods and spherical nanoparticles, can control solid state diffusion mechanisms over a long range, leading to extreme microstructural diversity.